Реакцiя лiмфоїдних органiв мишей на тейхоєву кислоту Staphylococcus aureus Wood 46 у нормi i при пухлинному ростi - Скiвка, Л.М.; Позур, В.В.; Сенчило, Н.В.; Рудик, М.П.; Фурзiкова, Т.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The effects of teichoic acid from cell walls of S. aureus Wood 46 on the weight indices and the cellularity of lymphoid organs in normal mice and mice with Lewis lung carcinoma are investigated. Changes of the cytomorphologic characteristics of immune system organs do not depend on the dose of teichoic acid in intact mice and are inversely proportional to the dose of teichoic acid in tumor-bearing mice. The most immunogenic dose of teichoic acid was 1µg/g for intact mice and 2µg/g for mice with Lewis lung carcinoma.